Hydrogen Sulfide Inhibits High Glucose-Induced sFlt-1 Production via Decreasing ADAM17 Expression in 3T3-L1 Adipocytes - Tian-xiao Hu; Gang Wang; Wei Wu; Lu Gao; Qing-ying Tan; Jing Wang (International Journal of Endocrinology)
Hydrogen sulfide (H2S) has recently been identified as an endogenous gaseous signaling molecule. The aim of the present study was to investigate the effect of H2S on high glucose- (HG-) induced ADAM17 expression and sFlt-1 production in 3T3-L1 adipocytes. Firstly, we found that HG DMEM upregulated the expression of ADAM17 and production of sFlt-1 in 3T3-L1 adipocytes. Knocking down ADAM17 attenuated the effect of high glucose on sFlt-1 production in adipocytes. HG decreased the expression of CSE and 3-MST, as well as the endogenous H2S production. Furthermore, knocking down CSE and 3-MST significantly increased ADAM17 expression and sFlt-1 production. The addition of exogenous H2S through the administration of sodium hydrosulfide (NaHS) inhibited HG-induced upregulation of ADAM17 expression and sFlt-1 production. In conclusion, decreased expression of CSE and 3-MST and the subsequent decrease in H2S production contribute to high glucose-induced sFlt-1 production via activating ADAM17 in adipocytes. Exogenous H2S donor NaHS has a potential therapeutic value for diabetic vascular complications.